â€œJourney from Reality to Virtualityâ€: the Impact of Ict in Education - C B, Manjusha; V.Vijayalakshmi, Dr; S, Mohankumar (International Journal of Engineering and Technology, 2018)
World around is moving towards the technologically ruled phase where every sector has got the impact of the ICT. In such a scenario, educational system is also taking up a different sphere where technology is used in the process of teaching and learning. From turn the pages of the book, the milieu has become swipe the screen. Myriads of evolution are happening in the field of education making it reachable at all nook and corners. The objective of this research article is to torch out how ICT is used to enhance the process of learning in the most comfortable manner. From those alphabets to inculcating the human values, ICT serves as a platform to make learning easier. The inclusion of ICT in curriculum will serves the purpose of learning and it also helps those underprivileged to acquire knowledge through the developments in the educational schemes. To nail it down, this research critique is an attempt to elucidate how the virtual learning milieu triggers the process of learning making it productive and enjoyable.Â